Sulfur nanoparticles synthesis and characterization from H2S gas, using novel biodegradable iron chelates in w/o microemulsion - Deshpande, Aniruddha S.; Khomane, Ramdas B.; Vaidya, Bhalchandra K.; Joshi, Renuka M.; Harle, Arti S.; Kulkarni, Bhaskar D. (Nanoscale Research Letters, 2008)
Sulfur nanoparticles were synthesized from hazardous H2S gas using novel biodegradable iron chelates in w/o microemulsion system. Fe3+-malic acid chelate (0.05 M aqueous solution) was studied in w/o microemulsion containing cyclohexane, Triton X-100 and n-hexanol as oil phase, surfactant, co-surfactant, respectively, for catalytic oxidation of H2S gas at ambient conditions of temperature, pressure, and neutral pH. The structural features of sulfur nanoparticles have been characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), energy dispersive spectroscopy (EDS), diffused reflectance infra-red Fourier transform technique, and BET surface area measurements. XRD analysis indicates the presence of alpha-sulfur. TEM analysis shows that the morphology of sulfur nanoparticles synthesized in w/o microemulsion system is nearly uniform in size (average particle size 10 nm) and narrow particle size distribution (in range of 5-15 nm) as compared to that in aqueous surfactant systems. The EDS analysis indicated high purity of sulfur (> 99%). Moreover, sulfur nanoparticles synthesized in w/o microemulsion system exhibit higher antimicrobial activity (against bacteria, yeast, and fungi) than that of colloidal sulfur.
Keywords: Antimicrobial activity; H2S gas; iron chelates; sulfur nanoparticles; w/o microemulsion

Strain improvement and statistical media optimization for enhanced erythritol production with minimal by-products from candida magnoliae mutant R23 - Savergave, Laxman S.; Gadre, Ramchandra V.; Vaidya, Bhalchandra K.; Narayanan, Karthik (Biochemical Engineering Journal, 2011)
Mutants of Candida magnoliae NCIM 3470 were generated by ultra-violet and chemical mutagenesis to enhance erythritol production. The mutants were screened for higher reductase activity on agar plates containing high concentration of glucose and 2,3,5-triphenyl tetrazolium chloride (TTC). One of the mutants named as R23 gave maximum erythritol production, 60.3 g L(-1), compared to 14 g L(-1) of the parent strain. Glucose and yeast extract were identified as critical medium components which decide the ratio of polyols produced, mainly erythritol, mannitol and glycerol. In order to enhance the production of erythritol and to minimize the production of mannitol and glycerol, a four component-five level-three response central-composite-rotatable-design (CCRD) of response surface methodology (RSM) model was used. The optimum medium composition for erythritol production was found to contain (g L(-1)) glucose 238, yeast extract 9.2, KH(2)PO(4), 5.16 and MgSO(4) 0.23. Moreover, erythritol production was studied in a 10 L fermentor in batch and fed-batch mode using RSM optimized medium. In fed-batch fermentation, 87.8 g L(-1) erythritol was produced with 31.1% yield, without formation of any other polyols. Thus present study involving strain improvement followed by media and process optimization resulted in 6.2-fold increase in erythritol production and 3.4-fold increase in the yield. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Candida magnoliae; Erythritol; Fermentation; Metabolite over-production; Modelling; Optimization